Writing security tools and exploits - Foster, James C. (Syngress, 2006)
Focusing on vulnerability and security code, this book is an educational reference for security professionals and software developers. It accompanies a CD, which contains a copy of the Hacker Code Library v1.0. The Hacker Code Library includes multiple attack classes and functions that are used to create security programs and scripts.